Basic Cell Culture Protocols - Helgason, Cheryl D.; Miller, Cindy L.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
At some point in their careers, virtually every scientist and technician, as well as many medical professionals, regardless of their area of specialization have a need to utilize cell culture systems. Updating and significantly expanding upon the previous editions, Basic Cell Culture Protocols, Fourth Edition provides the novice cell culturist with sufficient information to perform the basic techniques, to ensure the health and identity of their cell lines, and to be able to isolate and culture specialized primary cell types. The intent of this extensive volume is to generate a valuable resource containing clear methodologies pertinent to current areas of investigation, rather than attempting to educate cell culturists on specific cell types or organ systems.  Written in the highly successful Methods in Molecular Biology™, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and up-to-date, Basic Cell Culture Protocols, Fourth Edition compiles the essential techniques needed to approach this vital laboratory activity with full success.
1. Detection of Mycoplasma Contaminations -- 2. Eradication of Mycoplasma Contaminations -- 3. STR DNA Typing of Human Cell Lines: Detection of Intra- and Interspecies Cross-Contamination -- 4. Classical and Molecular Cytogenetic Analysis -- 5. Fluorescent In Situ Hybridization (FISH) of DNA Probes in the Interphase and Metaphase Stages of the Cell Cycle -- 6. The Development of T Lymphocytes in Fetal Thymus Organ Culture -- 7. Generation, Isolation, and Engraftment of In Vitro-Derived Human T Cell Progenitors -- 8. In Vitro Generation of Human T Regulatory Cells: Generation, Culture, and Analysis of FOXP3-Transduced T Cells -- 9. Simultaneous Cloning and Selection of Hybridomas and Transfected Cell Lines in Semisolid Media -- 10. Isolation and Characterization of Mouse Side Population Cells -- 11. Stem Cell Identification by DyeCycle Violet Side Population Analysis -- 12. Isolation and Characterization of Cancer Stem Cells In Vitro -- 13. Ex Vivo Differentiation of Cord Blood Stem Cells into Megakaryocytes and Platelets -- 14. Generation and Characterization of Murine Alternatively Activated Macrophages -- 15. Human Long Term Culture Initiating Cell (LTC-IC) Assay -- 16. Long Term Culture Initiating Cell (LTC-IC) Assay for Mouse Cells -- 17. Colony Forming Cell Assays for Human Hematopoietic Progenitor Cells -- 18. Studying Leukocyte Recruitment Under Flow Conditions -- 19. Generation and Establishment of Murine Adherent Cell Lines -- 20. Isolation, Enumeration, and Expansion of Human Mesenchymal Stem Cells in Culture -- 21. Isolation and Culture of Mesenchymal Stem Cells from Mouse Compact Bone -- 22. Generation of a Pool of Human Platelet Lysate (pHPL) and Efficient Use in Cell Culture -- 23. In Vitro Methods to Culture Primary Human Breast Epithelial Cells -- 24. Human Prostate Epithelial Cell Cultures -- 25. Enzymatic Dissociation, Flow Cytometric Analysis, and Culture of Normal Mouse Mammary Tissue -- 26. Isolation and Characterization of Human Hair Follicle Epithelial Cells -- 27. Co-Cultivation of Human Oral Keratinocytes and Human Osteoblast-Like Cells -- 28. Isolation and Culture of Skeletal Muscle Myofibers as a Means to Analyze Satellite Cells -- 29. Hepatic Differentiation of Embryonic Stem Cells by Murine Fetal Liver Mesenchymal Cells -- 30. Methods to Culture, Differentiate, and Characterize Neural Stem Cells from the Adult and Embryonic Mouse Central Nervous System -- 31. Feeder-Independent Culture Systems for Human Pluripotent Stem Cells -- 32. Formation of Embryoid Bodies from Human Pluripotent Stem Cells Using AggreWell™ Plates -- 33. Techniques in Embryoid Body Formation from Human Pluripotent Stem Cells.
Keywords: Cell biology; Cell culture; Cell Biology; Cell Culture